Higher fish biomass inside than outside marine protected areas despite typhoon impacts in a complex reefscape. (January 2020) - McClure, Eva C.; Sievers, Katherine T.; Abesamis, Rene A.; Hoey, Andrew S.; Alcala, Angel C.; Russ, Garry R.
Abstract: No-take marine protected areas (MPAs) are an important tool for conserving marine biodiversity and managing fisheries. However, with increasing environmental change driven by local and global stressors, it is critical to understand whether MPAs can continue to provide social, economic and conservation benefits in the long-term. Here, we compare coral reef benthic and fish assemblages across 17 paired MPA-fished control sites on three heavily populated, high elevation "mainland" islands, and four lowly populated, low elevation "offshore" islands that differed in their exposure to recent typhoons. Despite lower cover of macroalgae in MPAs compared to fished areas, especially on mainland islands, there were no consistent differences in benthic assemblages or total hard coral cover between paired MPA and fished reefs. Typhoons had severe negative effects on live hard coral cover, regardless of island type or MPA protection, and typhoon impacted reefs supported different fish assemblages and lower total biomass of fish, compared to non-impacted reefs. Although fish assemblage structure and total biomass differed between mainland and offshore islands, MPAs consistently supported a higher total biomass of fish than fished areas, with the magnitude of the MPA effect lower on typhoon impacted reefs. Our findings suggest that despite inherent differences in environmental conditions between mainland and offshore island coral reefs, MPAs can provide benefits to fish biomass, even when reefs are affected by typhoons. The development of management strategies that incorporate sound coastal land-use practices, while positioning MPAs in areas less prone to typhoon impact, will provide MPAs the best chance of success if climatic extremes increase.